Analisis Pembangkit Listrik Berbasis Flywheel - Jumadi Tangko; Remigius Tandioga; Ismail Djufri; Riza Haardiyanti (Jurnal Teknik Mesin Sinergi, 2019)
Flywheel is a rotating mechanical device, which is generally used on four-wheeled vehicles. Flywheel has a moment of inertia that is able to withstand changes in rotational speed. The energy in flywheel is mechanical energy. This mechanical energy will be converted by generators into electrical energy. At the flywheel-based power plant, tests are carried out in the form of rotation, the generator power of the generator under no load or load conditions, and the time needed for this generator to survive. The results showed that the ability of the flywheel-based power plant in the condition without a backup supply to the motor in the condition of a generator without a load is able to generate power of 860.1 W for 22 seconds, while in a load-bearing generator capable of generating electricity by 708.75 W for 18 seconds